(untitled) (Actualizaciones en Sida e Infectología, 2024)
Introduction Leptospirosis is an emerging zoonotic disease that poses a public health problem. Renal failure, thrombocytopenia, and respiratory involvement have been described as predictors of mortality. Objectives To describe the clinical, radiological, and laboratory characteristics of hospitalized individuals with leptospirosis and evaluate predictors of poor clinical outcomes (PCO). Materials and methods A prospective cohort study was conducted including patients with leptospirosis admitted to a hospital in the city of Santa Fe between 1997 and 2022. PCO was defined as admission to the Intensive Care Unit (ICU), requirement for mechanical respiratory assistance (MRA), and/or death. The chi-square test, Student’s t-test, or Mann-Whitney U test were used as appropriate. A binary logistic regression was performed with variables having p<0.05. Results 101 patients were included, 87.1% (n=88) were males, with a median age of 29 (IQR 44-20) years. Fever was the most common symptom [83.2% (n=84)], followed by digestive involvement [62.4% (n=63)]. The most frequent laboratory abnormalities were elevated erythrocyte sedimentation rate [91.9% (n=79)] and leukocytosis [61% (n=61)]. PCO was observed in 25.7% (n=26) of patients, with 25.7% (n=26) admitted to the ICU, 13.9% (n=14) requiring MRA, and 5% (n=5) resulting in death. The presence of thrombocytopenia (OR=13.3, 95% CI 2-80), abnormalities in chest X-rays (OR=33.5, 95% CI 5-225), and absence of headache (OR=6.8, 95% CI 1-32) were predictors of PCO. Conclusions Consistent with the literature, pulmonary involvement and thrombocytopenia are independent risk factors for poor clinical outcomes. In our series, the presence of headache was a protective symptom.